2009
DOI: 10.1126/science.1168245
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Ocean Wave Energy

Abstract: A body of literature quantifying wave attenuation through vegetation has developed within the last few decades and serves as the foundation for growing interest in wetlands for engineering with nature applications. Wave dissipation is shown to be highly variable, influenced by hydrodynamics, plant structure, and the interaction between the two. The current method of predicting wave dissipation often makes use of an empirical drag coefficient, which is given as a function of nondimensional flow parameter. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
106
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 6 publications
0
106
0
Order By: Relevance
“…They operate as the antenna of a radio receiver, which absorbs much more power from the wave than is incident on to its physical cross section [5]. Furthermore, optimal control theory has shown that multiple converters can exploit constructive interference to enhance power absorption [16].…”
mentioning
confidence: 99%
“…They operate as the antenna of a radio receiver, which absorbs much more power from the wave than is incident on to its physical cross section [5]. Furthermore, optimal control theory has shown that multiple converters can exploit constructive interference to enhance power absorption [16].…”
mentioning
confidence: 99%
“…There are successful initiatives in harvesting energy from temperature gradients (Tanner, 1995), tides (Rourke et al, 2010), both potential (Frau, 1993) and kinetic (Khan et al, 2009;Roberts et al, 2016), currents (Ponta and Jakovkis, 2008), salinity gradients (Ramon et al, 2011) and waves (Falcão, 2010;Muetze and Vining, 2006). Among these possibilities, the extraction of energy from gravity waves is considered one of the most efficient alternatives due to the total energy available in that form and the fact that it is more predictable than some other renewable sources such as aeolian and solar (Scruggs and Jacob, 2009). Although several kinds of wave can be described as gravity waves [tsunamis, tides and Kelvin waves, for instance], we refer to waves, or gravity waves, as those generated by the wind.…”
Section: Introductionmentioning
confidence: 99%
“…Between this range, the optimal location for power generation are often at depths between 40 and 100 m, once as the waves propagate into the shore, they are modified by bottom effects like refraction, diffraction, bottom friction and wave breaking, resulting in the dissipation of its energy in shallow areas, usually shallower than 40m (Falcão, 2010). Regarding waters deeper than 100 m, considered deep for this study, the limitation is related to impractical and uneconomical conditions to deploy a wave power plant and connect it to a shore-line station, due the long distance from the shore (Scruggs and Jacob, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An extremely abundant and promising source of energy exists in oceans. Among these forms of ocean energy, signficant opportunities and benefits have been identified in the area of ocean wave energy extraction [1,2]. Since the 1970s, researchers from all over the world have studied wave energy conversion (WEC) systems that can harness the motion of ocean waves and convert it into electrical energy [3].…”
Section: Introductionmentioning
confidence: 99%